Using genomic sequence information to increase conservation and sustainable use of crop diversity and benefit-sharing - Halewood, Michael; López Noriega, Isabel; Ellis, Dave; Roa, Carolina; Rouard, Mathieu; Hamilton, Ruaraidh S. (Mary Ann Liebert Inc, 2018)
This article describes how CGIAR centers and partners are using genomic sequence information to promote the conservation and sustainable use of crop genetic diversity, and to generate and share benefits derived from those uses. The article highlights combined institutional, and benefit-sharing-related challenges that need to be addressed to support expanded use of digital sequence information in agricultural research and development